The Kinerja Ekspor Cengkeh Indonesia Di Pasar India: Pendekatan Linear Approximate Almost Ideal Demand System (LA/AIDS) - Joaquina da Silva Pinto; Suharno Suharno; Amzul Rifin (Jurnal Agribisnis Indonesia, 2022)
The demand for Indonesian cloves in the Indian market fluctuated during 2010-2018, but in 2019-2020 the demand for Indonesian cloves increased due to India's high demand for clove commodities. This research is important considering that Indonesia is not the only country that fulfills India's demand for clove imports. This study aims to determine the competitive position of Indonesian cloves in the Indian market. The performance of Indonesian clove exports to the Indian market was analyzed using the Indian clove demand system by applying the Linearized Approximate Almost Ideal Demand System (LA/AIDS). The dependent variable was the share of the four exporting countries, and the independent variable was the price of cloves from Indonesia, Madagascar, Sri Lanka, and Comoros in the Indian market. The data used secondary time series data between 2010-2020. The analysis results showed that cloves from Indonesian, Madagascar, and Comoros are responsive to Indian expenditure changes. If there is a price change of Indonesian cloves, India will switch to Madagascar and Comoros cloves because the cloves of both countries have good quality. Increasing the exports volume of cloves with good quality, and reducing tariff will improve the Indonesian clove export performance in Indian market.